Mathematician Mečislovas Mačernis (1897–1968) as a pioneer of didactics in lithuania - Banionis, Juozas (Lietuvos matematikos rinkinys, 2016)
The National Pedagogical Institute (NPI), established in 1935, ensured the progress of education in Lithuania. NPI being one of the newest schools of higher education in the period of independent Lithuania committed itself not only to practical activity, i.e. preparing high professional quality teachers for primary schools, but to development of scientific activity, too. The Ministry of Education invited an experienced pedagogue, famous in preparing future teachers and the author of texts designed for teachers’ professional development, Mečislovas (Mečys) Mačernis who would work alongside with other founders of NPI for implementation of its double mission. M. Mačernis was born in the vicinity of the town Seda (Gedrimai village in Alsėdžiai parish) in Lithuania’s region Samogitia. In 1919, M. Mačernis finished Vilnius Lithuanian Gymnasium, and in 1920–1923 he studied mathematics and physics at Berlin University and Königsberg University. Later M. Mačernis was a teacher and director at Tauragė Teacher Training School. In 1930, he obtained the right, which was equivalent to the right of higher school graduates, to work as a teacher at high school. M. Mačernis could teach introductory subjects into philosophy and pedagogy. In 1935, M. Mačernis was invited to work as an inspector at NPI, and in 1937 he became NPI Director. In the period from 1935 to 1940, which was full of changes, M. Mačernis taught general methods (didactics), methods of geography, history and nature studies, methods of calculus and geometry, mathematics. Alongside with teaching a number of subjects to future teachers, M. Mačernis was active in science and development of pedagogical process. It is testified by M. Mačernis texts, i.e. scientific articles in NPI research collection “Pedagogical Chronicle”, the journal “Works of Education”, the books “Didactics” (3 parts, 1939–1940), and “Methods of Calculus and Geometry” (1940). Since 1928 M. Mačernis, following his own idea that the aim of the school is to prepare citizens who will be able to carry out their duties, strived to prepare teachers in specialized high schools in the same way as in Germany. The vision of a new school model was based on the experience of Western world that he familiarized himself with during studies. That is why the course of didactics designed by M. Mačernis generalizes not only the achievements of Lithuanian schools but it also includes modern pedagogy. M. Mačernis promoted the idea of the exemplary school where future teachers could have school placement. In future teachers’ education M. Mačernis always highlighted the necessity to understand the history of the subject because “the process of finding the truth is the most important element in understanding the truth”. M. Mačernis invited the graduates to be creative, do not follow blindly textbooks but evaluate them critically. In teaching methods of mathematics M. Mačernis paid a lot of attention to overviewing the methods of teaching this subject. After psychological analysis of lesson components, he also created a new type of lesson, i.e. problem based lesson structure, which was new at that time in Lithuania. M. Mačernis thought that mathematics at school should be oriented towards its practical application insuring school mathematics integrity and relation to high school. Spreading of scientific ideas of modern didactics which were already popular in Western world but not in Lithuania could be considered as the biggest V. Mačernis’s input into education in Lithuania of the first half of the 20th century.